Microbiologically-Synthesized Nanoparticles and Their Role in Silencing the Biofilm Signaling Cascade - Lahiri, Dibyajit; Nag, Moupriya; Sheikh, Hassan I.; Sarkar, Tanmay; Edinur, Hisham Atan; Pati, Siddhartha; Ray, Rina Rani (Frontiers in Microbiology, 2021)
Emergence of bacterial resistance to antibiotics has led to the search for alternate antimicrobial treatment strategies. Engineered nanoparticles (NPs) for efficient penetration within the living system became more common in the world of health and hygiene. The use of microbial enzymes/proteins as a potential reducing agent for synthesizing NPs has increasing rapidly in comparison to physical and chemical methods. It is a fast, environmentally safe, and cost-effective approach. Amongst the biogenic sources, fungi and bacteria are preferred not only for their ability to produce higher titer of reductase enzyme to convert the ionic forms into their nano forms, but also for their convenience in cultivating and regulating the size and morphology of the synthesized NPs, which can effectively reduce the cost for large scale manufacture. Effective penetration through exopolysaccharides of biofilm matrix enables the NPs to stop the bacterial growth. Biofilm is the consortia of sessile groups of microbial cells possessing the ability of adhering to biotic and abiotic surfaces with the help extracellular polymeric substances and glycocalyx. These biofilms on one hand are the root causes of various chronic diseases and on the other hand lead to biofouling on medical devices and implants. The NPs enter the biofilm and affect the quorum sensing gene cascades and thereby hamper the cell-to-cell communication mechanism and finally inhibit biofilm synthesis. This review focuses on the microbial nano-techniques that are used for the production of various metallic and non-metallic nanoparticles and their “signal jamming effects” to inhibit biofilm formation. Detailed analysis and discussion is given to their interactions with various types of signal molecules and the genes responsible for the development of biofilm.